Automatic solar tracker for poultry farm / Amir Khushyrie Amiruddin ... [et al.] - Amiruddin, Amir Khushyrie; Mohd Hassan, Nur Sabrina; Abd Rahim, Alhan Farhanah; Radzali, Rosfariza (2022)
The poultry farm is one of the industries that use a lot of electricity, and this could lead to global warming and greenhouse effects. Numerous poultry farmers have used solar power to operate their farms. The solar panel that they install is a fixed installation at a certain angle. This has caused the amount of energy absorbed by the solar panel to be lessened making the entire potential of the solar panel wasted. A solar tracker that could automatically track the sunlight is needed to not waste the potential of this renewable energy. The main goal of this project is to produce a design that could automatically track the sunlight with the help of LDR sensors. When the LDR sensors sense the sunlight, it will cause the solar panel to turn to face the sunlight and trap as much sunlight as it can before the lipo charger battery module converts the energy to electrical energy and stores it in the Li-ion battery. This project has a total of 6 inputs (solar panel, lipo battery charger module, Li-ion battery, switch button, LDR sensors, and temperature sensor) and 4 outputs (servo motor, motor driver, DC motor, and LEDs).